Characterization of Bladder Selectivity of Antimuscarinic Agents on the Basis of In Vivo Drug-Receptor Binding - Yamada, Shizuo (Korean Continence Society, 2012)
The in vivo muscarinic receptor binding of antimuscarinic agents (oxybutynin, solifenacin, tolterodine, and imidafenacin) used to treat urinary dysfunction in patients with overactive bladder is reviewed. Transdermal administration of oxybutynin in rats leads to significant binding of muscarinic receptors in the bladder without long-term binding in the submaxillary gland and the abolishment of salivation evoked by oral oxybutynin. Oral solifenacin shows significant and long-lasting binding to muscarinic receptors in mouse tissues expressing the M(3) subtype. Oral tolterodine binds more selectively to muscarinic receptors in the bladder than in the submaxillary gland in mice. The muscarinic receptor binding of oral imidafenacin in rats is more selective and longer-lasting in the bladder than in other tissues such as the submaxillary gland, heart, colon, lung, and brain, suggesting preferential muscarinic receptor binding in the bladder. In vivo quantitative autoradiography with (+)N-[(11)C]methyl-3-piperidyl benzilate in rats shows significant occupancy of brain muscarinic receptors with the intravenous injection of oxybutynin, solifenacin, and tolterodine. The estimated in vivo selectivity in brain is significantly greater for solifenacin and tolterodine than for oxybutynin. Imidafenacin occupies few brain muscarinic receptors. Similar findings for oral oxybutynin were observed with positron emission tomography in conscious rhesus monkeys with a significant disturbance of short-term memory. The newer generation of antimuscarinic agents may be advantageous in terms of bladder selectivity after systemic administration.